Bevingede ord? I anledning af Bevingede ORD, 7. udgave - Brink, Lars; Farø, Ken (LexicoNordica, 2007)
On the occasion of a new edition of the well-known Danish dictionary of “Bevinge-de ORD”, edited by Pia Jarvad, we examine the concept of “familiar” (or “stock”) quotations quite thoroughly. This dictionary is extremely popular because of its many interesting descriptions of the text history of specific words and expressions. Our main goal is to show that bevingede ord are in fact a proper linguistic object that exposes itself to scientific scrutiny. Therefore, the title of the dictionary is not ade-quate as the familiar quotations make up only 32% of the contents. We try to explain what might have gone wrong on the long way from linguistic categorization to dic-tionary naming. This does not mean that we do not find the dictionary useful to a number of certain user needs, on the contrary.